Face-to-face bullying in and outside of schools and cyberbullying are associated with suicidality in Kenyan high school students: a public health issue - David M. Ndetei; Victoria Mutiso; Jenelle R. Shanley; Christine Musyimi; Pascalyne Nyamai; Timothy Munyua; Tom L. Osborn; Natalie E. Johnson; Sonja Gilbert; Anne Abio; Afzal Javed; Andre Sourander (BMC Psychiatry, 2024)
Abstract Background Childhood bullying has been classified as a major public health concern by WHO, with negative effects on the health education and social outcomes of both bullies and victims. There is no current Kenyan data on the prevalence of face-to-face bullying and cyberbullying co-occurring in the same cohort of youth and how they are associated with different aspects of suicidality and socio-demographic characteristics. This study aims to fill these gaps in the Kenyan situation so as to inform current policy and practice. Methodology This cross-sectional study involved 2,652 students from ten secondary schools in Kenya, selected from three regions representing different levels of public funded schools and socioeconomic spaces. The outcome variable was derived from the questionnaire which asked students questions related to self-harm, suicide thoughts, plans, and attempts. Predictor variables were based on response on experience of bullying in school, out of school, at home, and cyberbullying. Other variables such as gender, age, family background, and class were also collected from the self-reported questions. Data were analyzed using SPSS version 25, with descriptive summary statistics and chi-square tests used to examine variables, and logistic regression analysis used to determine the associations between suicidality and experience of bullying. Results The mean age was 16.13 years. More than half of the participants were male, with the largest proportion living in rural areas. Face-to-face bullying was more prevalent than cyberbullying, with 82% of participants experiencing bullying and 68% experiencing it almost daily in the past six months. Both face-to-face bullying and cyberbullying were associated with suicidal thoughts, plans, and attempts. Predictors of suicidal attempts included being bullied outside of school and being a victim of group bullying, while being bullied every day and being bullied by adult men were predictors of suicidal attempts in cyberbullying. Conclusion There is a high prevalence of face-to-face bullying both in and outside schools. There is also a high prevalence of cyberbullying. Both face-to-face and cyberbullying are associated with suicidality in Kenyan high school students.